2016
DOI: 10.1073/pnas.1602916113
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and mechanism of ultrafast water–protein interactions

Abstract: Protein hydration is essential to its structure, dynamics, and function, but water-protein interactions have not been directly observed in real time at physiological temperature to our awareness. By using a tryptophan scan with femtosecond spectroscopy, we simultaneously measured the hydration water dynamics and protein side-chain motions with temperature dependence. We observed the heterogeneous hydration dynamics around the global protein surface with two types of coupled motions, collective water/side-chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

28
164
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(195 citation statements)
references
References 37 publications
28
164
0
3
Order By: Relevance
“…One of the four partly hydrophobic solutes studied by Qvist and Halle (17) was N-acetyl-leucine-N-methylamide, which should have an alkane-like hydration shell. See also the recent NMR study of protein hydration shells by Zhong and coworkers (18).…”
Section: Possible Relation Between the Very Short (Approximately Picomentioning
confidence: 99%
“…One of the four partly hydrophobic solutes studied by Qvist and Halle (17) was N-acetyl-leucine-N-methylamide, which should have an alkane-like hydration shell. See also the recent NMR study of protein hydration shells by Zhong and coworkers (18).…”
Section: Possible Relation Between the Very Short (Approximately Picomentioning
confidence: 99%
“…Several additional important results have emerged from the studies reported in ref. 6, which deserve further discussion and scrutiny. First, dynamics probed are sensitive not only to the exposure of the Trp residue but also to the polar character of the surrounding medium.…”
mentioning
confidence: 96%
“…These have been derived from experiments that use different techniques, different probes, and different protein molecules (3)(4)(5). The paper by Qin et al (6) discusses results of detailed experimental (and simulation) studies of water at the surface of a specific protein, DNA polymerase IV (Protein Data Bank ID code DPo4). The experimental method used is time-dependent fluorescence Stokes shift (TDFSS), which is a popular tool in the study of dipolar solvation dynamics (1).…”
mentioning
confidence: 99%
See 2 more Smart Citations